Toxoplasmosis Among 38 751 Hematopoietic Stem-cell Transplant Recipients: A Systematic Review of Disease Prevalence and a Compilation of Imaging and Autopsy Findings. Issue 12 (4th February 2021) - Contopoulos-Ioannidis, Despina G.; Cho, Stephanie M.; Bertaina, Alice; Leung, Ann N.; Fischbein, Nancy; Lanzman, Bryan; Schwenk, Hayden T.; Montoya, Jose G.
Abstract : Supplemental Digital Content is available in the text. Abstract : Background: Toxoplasmosis in hematopoietic stem-cell transplant (HSCT) recipients can be life threatening if not promptly diagnosed and treated. Methods: We performed a systematic review (PubMed last search March 29, 2020) of toxoplasmosis among HSCT recipients and calculated the toxoplasmosis prevalence across studies. We also created a compilation list of brain imaging, chest imaging, and autopsy findings of toxoplasmosis among HSCT recipients. Results: We identified 46 eligible studies (47 datasets) with 399 toxoplasmosis cases among 38 751 HSCT recipients. There was large heterogeneity in the reported toxoplasmosis prevalence across studies, thus formal meta-analysis was not attempted. The median toxoplasmosis prevalence among 38 751 HSCT recipients was 2.14% (range 0%–66.67%). Data on toxoplasmosis among at-risk R + HSCT recipients were more limited (25 studies; 2404 R + HSCT recipients [6.2% of all HSCT recipients]), although the median number of R + HSCT recipients was 56.79% across all HSCT recipients. The median toxoplasmosis prevalence across studies among 2404 R + HSCT was 7.51% (range 0%–80%) versus 0% (range 0%–1.23%) among 7438 R – HSCT. There were limited data to allow meaningful analyses of toxoplasmosis prevalence according to prophylaxis status of R + HSCT recipients. Conclusions: Toxoplasmosis prevalence among HSCT recipients is underestimated. The majority of studies report toxoplasmosis prevalence among all HSCT recipients rather than only among the at-risk R + HSCT recipients. In fact, the median toxoplasmosis prevalence among all R +/ /R – HSCT recipients is 3.5-fold lower compared with the prevalence among only the at-risk R + HSCT recipients and the median prevalence among R + HSCT recipients is 7.51-fold higher than among R – HSCT recipients. The imaging findings of toxoplasmosis among HSCT recipients can be atypical. High index of suspicion is needed in R + HSCT recipients with fever, pneumonia, or encephalitis.